The Study of Russian Religious Philosophy in Freiborg (Afterword of the Translator) - Tsygankov, А.С. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2018)
A brief afterword to the translation of the article “Leo Tolstoy and Russian Religious Philosophy” written by modern Swiss researcher Regula M. Tsvalin presents the current issue investigation on the history of Russian Thought. This research was carried out at the Institute of Ecumenical Studies of Theological Faculty of Fribourg University (Switzerland). The Sergij Bulgakov Research Center (German Forschungsstelle Sergij Bulgakov) was founded on the basis of the University of Friborg in 2011. Translation, commenting and publication of the German-language S.N. Bulgakov’s collected edition (German Werkausgabe von Sergij Bulgakov in deutscher Sprache) are main tasks of Sergij Bulgakov Research Center. Currently, the first three volumes of Russian thinker’s collected edition included “Philosophy of the economy”, “Nature in the philosophy of V.l. Solovyov” (1 volume) and “Autobiographical notes” (2 volumes) have been prepared and published by their members. The third volume, appeared at the end of 2017, includes a bibliography of S.N. Bulgakov’s works. This biography claims to be the most complete and precise for today. In addition, the reader will be also able to get acquainted with other research areas developed at Sergij Bulgakov Research Center covered the history of Russian Thought and have no direct relationship to the creativity and personality of national philosopher-theologian.